Neutrophil extracellular traps aggravate uremic cardiomyopathy by inducing myocardial fibroblast pyroptosis - Ying Xu; Yan Ren; Wenli Zou; Minmin Wang; Xianyun Ye; Wei Shen (Scientific Reports)
Abstract Uremic cardiomyopathy (UCM) is a leading cause of death in patients with chronic kidney disease. This study aimed to explore the role and underlying mechanisms of neutrophil extracellular traps (NETs) in UCM. A UCM mouse model was constructed using 5/6 nephrectomy and treated with the NET inhibitor DNaseI. Cardiac fibroblasts were incubated with 200 ng/mL of NETs to establish an in vitro model. Physiological parameters of mice were measured, and commercial kits were used to detect MPO-DNA, IL-1β, and IL-6 levels. Hematoxylin-eosin and TUNEL staining were performed to evaluate myocardial injury and apoptosis. Immunofluorescence was used to detect MPO, CitH3, and caspase-1 expression. Sytox Green staining and CCK-8 assay were applied to assess NET formation and determine the optimal NET concentration. Western blot was conducted to detect collagen1, α-SMA, NLRP3, GSDMD-N, and caspase-1 expression. Transmission electron microscopy was performed to observe pyroptosis. UCM mice exhibited impaired kidney and cardiac function, indicating the successful establishment of the UCM model. MPO-DNA levels were elevated in UCM mice, suggesting NET formation. DNaseI treatment significantly reduced MPO and CitH3 expression, inhibiting NET formation in UCM mice. NET inhibition improved renal function and alleviated cardiac injury. Furthermore, NET inhibition reduced inflammation, apoptosis, and pyroptosis in UCM mice. Neutrophils isolated from UCM mice, as well as PMA, induced NET formation. NETs significantly enhanced fibrosis and pyroptosis in myocardial fibroblasts. NETs may promote UCM progression by inducing pyroptosis in myocardial fibroblasts.